Knowledge, awareness and dietary practice on urolithiasis among general population in Kuantan, Pahang, Malaysia: preliminary findings - Sowtali, Siti Noorkhairina; Mohd Arifin, Siti Roshaidai; Nazli, Nor Syawanidamia; Mohd Shukri, Nor Azwani; Khattak, Muhammad Muzaffar Ali Khan; Ab Rashid, Islah Munjih; Muhamad, Suhana; Adzali, Fatin Noraliah (2020)
Background: To date, there is a lack of published studies on assessing the level of knowledge, awareness and practice of dietary pattern particularly on urolithiasis among patients or general population. Aims: This study will provide baseline information on the level of knowledge, awareness and dietary practice among general population in Kuantan, Pahang Methods: Respondents (n=30) were conveniently recruited within 10 kilometres radius of Kuantan city between January to February 2020. Ethical approval was obtained from Kuantan Municipal Council prior data collection. Respondents were given adequate time to complete the survey. The data were obtained using semi-guided administered questionnaires consisted of four parts: socio-demographic data, lifestyle and clinical history (Part A); attitude and awareness on dietary practice regarding urolithiasis (Part B); food frequency questionnaire on urolithiasis (Part C) and level of knowledge on urolithiasis (Part D). The items in the questionnaire were developed based on the authors’ expertise, previous literature reviews and pre-test experience among 15 patients with urolithiasis. Content validity index and Cronbach alpha value were calculated for validity and reliability. The data was analysed descriptively using Statistical Package for Social Sciences version 25. Results: Majority of the respondents were women (70%), Malay (83.3%), mean age of 33.97 (±9.27), married (63.3%), completed higher education level (60%), working with government sector (33.3%) and have fixed monthly income (53.3%). Some of them had hypertension (n=4), diabetes (n=1), gout (n=1) and intestinal problem (n=1). Majority (80%) claimed having no family history of urolithiasis, consumed alcohol (10%), exercise with average frequency 2-3 times/week (46.7%) and heard about urolithiasis from healthcare worker (46.7%). The respondents’ awareness about urolithiasis considered good [81.23 (±9.98)] but having poor knowledge score [2.70 (±1.149)]. Majority preferred wholemeal bread, white rice, chicken meat, mackerel fish, chicken egg, apple, carrot, mustard leave and fresh milk in daily intake. Lesser plain water intake than standard requirement was noticed among respondents. Seasoning powder was commonly used for seasoning. Conclusions: Overall, the general population of Kuantan, Pahang was aware about urolithiasis disease but need more input on dietary aspect in terms of knowledge and food choice. More awareness campaign shall be held in the future.